Dispersion of sediment in two-phase turbulence flows - Jiang, Junsheng (2008)
In this report, the basic two-phase conservation equations are applied to analyze two configurations of sediment-laden flows: (a) an open channel flow with suspended sediment and (b) a vertical sediment-laden jet.